Cigarette smoke condensate may disturb immune function with apoptotic cell death by impairing function of organelles in alveolar macrophages. (October 2018) - Park, Eun-Jung; Lee, Hong-Soo; Lee, Sang Jin; Park, Yoo-Jin; Park, Son-Il; Chang, Jaerak; Lee, Kyuhong
Abstract: Considering that cigarette smoke condensate (CSC) is primarily absorbed through the alveoli in the lungs, herein, we used a mouse alveolar macrophage cell line (MH-S cells). After 24 h exposure, CSC decreased dose-dependently cell viability accompanying an increase in intracellular ROS and NO level. CSC structurally or functionally damaged organelles including mitochondria, ER and lysosome and enhanced the expression of proteins related to apoptosis, ER stress and DNA damage accompanying an elevated proportion of annexin V-bound cells. Meanwhile, the expression of certain proteins related to mitochondrial dynamics (OPA1 and DRP1) and autophagy (ATG5) did not overall show significant dose-dependent change in cells exposed to CSC. More importantly, conversion of LC3-I to LC3B-II, a representative marker for autophagy, was also unclear. Considering that intracellular organelles work together in harmony to perform defense mechanism against foreign bodies, we investigated changes in immune response following CSC exposure. The level of IFN-γ and MIP-1α was elevated in CSC-exposed cells, whereas the MCP-1α level decreased. The expression of chemokine receptors (CD195 and CXCR2) and an adhesion molecule (CD54) increased by CSC treatment, the expression of certain antigen presentation-related proteins (MHC class II, CD40, and CD80) were also enhanced. Meanwhile, the expression of CD86, a co-stimulatory molecule for antigen presentation, dose-dependently decreased. In conclusion, we suggest that CSC may induce apoptotic cell death and disturbance in host defense mechanisms by impairing function of cellular components. Highlights: We focused on toxicity of amphoteric fraction (CSC) contained to cigarette smoke. CSC decreased cell viability with oxidative stress in alveolar macrophage cells Structural and functional damage of organelles was observed in CSC-exposed cells. Apoptotic cell death was induced accompanying incomplete autophagy signal. Expression of proteins working in host defense against foreign body was disturbed.